ICT solutions in Polish law firms - Chomiak, Iwona; Golusińska, Katarzyna; Kruczek, Jakub; Krajewski, Maciej (Narzędzia informacyjno-komunikacyjne wykorzystywane w polskich kancelariach prawnych, 2019)
Functioning on the market without the use of ICT solutions is nowadays impossible. Information and communication technologies are part of the image of modern organizations as a tool supporting business processes and also enabling smooth communication both within the organization and with the environment. The aim of this article is to review typology of information and communication solutions that are used by a very specific group of organizational entities such as law firms. Due to the specificity of the entities whose functioning will be cited in the article, it was necessary for the authors of the article to adopt a broad perspective of the discussed solutions. Therefore, the article presents IT tools supporting the distribution of legal knowledge which benefits not only law firms but which is also accessible to all other business entities, as well as the directions and possibilities of ICT solutions supporting the work of law firms are indicated. The research tools used by the authors include literature research, analysis of IT solutions available in the area of distribution of legal information sources, and many years of professional experience of the authors of the article
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 4 (54), s. 9-18
Keywords: informatyka ekonomiczna